A behavioural study of hydrothermally derived novel alumina/magnesia/hydroxyapatite (Al2O3/MgO/HA) bioceramic nanocomposite. (September 2022) - Alinda Shaly, A.; Hannah Priya, G.; Mahendiran, M.; Mary Linet, J.
Abstract: Regeneration and regrowth of human bones is a gradual and time-consuming process. Therefore scaffolds are required to hold the bones in position and give them time to heal well. Though hydroxyapatite (HA) is a potential candidate, its weak mechanical nature has made it undesirable. To overcome this hurdle, a novel nanocomposite of HA with alumina (Al2 O3 ) and magnesia (MgO) was prepared by hydrothermal method in this study. The constitution, composition and conformation of the Al2 O3 /MgO/HA nanocomposite were affirmed via X-ray Diffraction (XRD), Fourier-Transform Infra-Red (FTIR) and imaging tests. Vicker's hardness test evinces the mechanical calibre of the nanocomposite. A perspective load-displacement analysis was done by means of Onitsch and Kick's power laws. The nanocomposite excelled above par with a hardness of 5.19 GPa and fracture toughness of 1.27 MPam 1/2 . This holistic progress makes this nanocomposite a very desirable bone implant material.